2015
DOI: 10.1103/physreva.91.023815
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-dimensional solitons supported by singular modulation of quadratic nonlinearity

Abstract: We introduce a model of one-and two-dimensional (1D and 2D) optical media with the χ (2) nonlinearity whose local strength is subject to cusp-shaped spatial modulation, χ (2) ∼ r −α , with α > 0, which can be induced by spatially nonuniform poling. Using analytical and numerical methods, we demonstrate that this setting supports 1D and 2D fundamental solitons, at α < 1 and α < 2, respectively. The 1D solitons have a small instability region, while the 2D solitons have a stability region at α < 0.5 and are unst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…In 1995, optical solitons in a quadratic bulk material were observed by Torruellas et al [23] , and existence of the solitons in χ 2 waveguide were observed experimentally by Schiek et al [24] in 1996. These original results have since been corroborated and extended in many follow-up experiments [25][26][27][28][29][30], demonstrating that quadratic solitons can exist in both the spatial and the temporal domains in waveguides or bulk materials [31][32][33][34]. One of the distinguished properties of quadratic nonlinear media is that it provides stable multidimensional pulse propagation without collapse in any dimension [31,32,35].…”
Section: Introductionmentioning
confidence: 70%
“…In 1995, optical solitons in a quadratic bulk material were observed by Torruellas et al [23] , and existence of the solitons in χ 2 waveguide were observed experimentally by Schiek et al [24] in 1996. These original results have since been corroborated and extended in many follow-up experiments [25][26][27][28][29][30], demonstrating that quadratic solitons can exist in both the spatial and the temporal domains in waveguides or bulk materials [31][32][33][34]. One of the distinguished properties of quadratic nonlinear media is that it provides stable multidimensional pulse propagation without collapse in any dimension [31,32,35].…”
Section: Introductionmentioning
confidence: 70%
“…As mentioned above, a basic result reported in Ref. [27] is that these equations generate fundamental (zerovorticity) localized states pinned to the singular-modulation peak at α < 2, and these states have a stability area at α < 0.5. Under this condition, they tend to be stable and unstable, respectively, at smaller and larger values of the total power, P , at all values of the mismatch, see Eq.…”
Section: The Modelmentioning
confidence: 81%
“…A discrete version of the localized quadratic nonlinearity was elaborated in the form of a linear lattice with one or two χ (2) -nonlinear sites embedded in it [26].While the delta-like modulation of the local χ (2) coefficient may not be easily realized in the experiment, a more realistic case of the 1D singular modulation, with χ (2) ∼ |x| −α and positive α, was introduced in Ref. [27]. It was found that this modulation format supports quadratic solitons, pinned to the singular peak, for α < 1 (the pinned modes vanish at α = 1), and they are chiefly stable.…”
mentioning
confidence: 99%
See 2 more Smart Citations